2022
DOI: 10.3389/fsurg.2022.901638
|View full text |Cite
|
Sign up to set email alerts
|

Effect Observation of Electro-Acupuncture Anesthesia Combined with General Anesthesia in Elderly Patients Undergoing Gastrointestinal Tumor Resection

Abstract: ObjectiveTo investigate the anesthetic effect of electro-acupuncture (EA) anesthesia combined with general anesthesia in elderly patients undergoing gastrointestinal tumor resection, and to analyze the effects of EA anesthesia on inflammatory factors, stress state and T lymphocyte subsets in elderly patients.MethodsTotal of 118 elderly patients who underwent gastrointestinal tumor resection in our hospital from June 2018 to March 2021 were selected and divided into the control group (59 cases) and the observat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 27 publications
0
3
0
Order By: Relevance
“…When acupuncture stimulation is applied to acupuncture points, it promotes releases special molecules, like opioid peptide, glutamate, and adenosine calcium, which alleviate pain on particular organs ( 43 ). Several clinical studies ( 11 , 19 , 45 , 46 ) have demonstrated that acupuncture anesthesia can effectively reduce the dosage of anesthetic drugs and the risk of adverse reactions in surgical applications, with minimal physiological intervention in patients. Adenosine, a neuromodulator with antinociceptive characteristics, is involved in the local analgesic effect of acupuncture and amplifies the rise in acupuncture-induced adenosine and its antinociceptive effect ( 47 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…When acupuncture stimulation is applied to acupuncture points, it promotes releases special molecules, like opioid peptide, glutamate, and adenosine calcium, which alleviate pain on particular organs ( 43 ). Several clinical studies ( 11 , 19 , 45 , 46 ) have demonstrated that acupuncture anesthesia can effectively reduce the dosage of anesthetic drugs and the risk of adverse reactions in surgical applications, with minimal physiological intervention in patients. Adenosine, a neuromodulator with antinociceptive characteristics, is involved in the local analgesic effect of acupuncture and amplifies the rise in acupuncture-induced adenosine and its antinociceptive effect ( 47 ).…”
Section: Discussionmentioning
confidence: 99%
“…In terms of indications, acupuncture anesthesia is being investigated not only for clinical anesthesia management but also for perioperative pain, nausea and vomiting, and other symptoms that can hasten patient recovery ( 51 ). In terms of applicable groups, it is being applied to special populations aimed at elderly, children and pregnant women ( 46 , 52 , 53 ). This approach complies with the principles of ERAS ( 54 ), an evidence-based, multimodal, and multidisciplinary approach to surgical patient care.…”
Section: Discussionmentioning
confidence: 99%
“…In patients with gastric cancer, acupuncture compound general anesthesia reduced the negative impacts on immune function based on obviously decreased levels of CD3 + , CD4 + and CD4 + /CD8 + after subtotal gastrectomy ( 79 ). Similarly, in patients following gastrointestinal tumor resection, EA compound general anesthesia had a satisfactory anesthetic effect and immunomodulatory function, which had lower levels of TNF-α, IL-6, and IL-1β and decreased levels of CD3 + , CD4 + and CD4 + /CD8 + ( 80 ). As for cancer-related fatigue, acupuncture was beneficial to improve the symptoms of fatigue and promote the absolute counts of CD3 + , CD4 + , CD8 + and CD4 + /CD8 + ( 81 ).…”
Section: Acupuncture In Regulating Immune Microenvironmentmentioning
confidence: 99%